Corrosion Problems in Incinerators and Biomass-Fuel-Fired Boilers. (11th May 2014) - Mudgal, Deepa; Singh, Surendra; Prakash, Satya
Abstract : Incinerators are widely used to burn the municipal waste, biowaste, wood, straw, and biomedical waste. Combustion of these types of waste results in generation of chlorides of sodium and potassium which may attack the metallic part of the incinerator. In biofuel-fired boilers, similar type of highly corrosive environment is present. Attempt has been made to review the corrosion problems and their solutions as per the available literature.